Increased chlorophyll efficiency of dark-adapted camellia foliage when treated with chlorine dioxide or hydrogen dioxide and blended with a non-ionic surfactant - Hammack, Heather Nicole, author; Newman, Steven E., advisor; Qian, Yaling, committee member; Pilon-Smits, Elizabeth, committee member (Colorado State University. Libraries, 2013)
Phytophthora ramorum is a major risk to interstate trade of nursery stock. This work focused on chemical oxidant chemistry as a disinfectant of nursery grown camellia plants. Disinfection of nursery stock is crucial for shipping, but the impact on plant health and phytotoxic responses are also important. To determine plant stress responses to applied chemical oxidants, we measured chlorophyll activity (PSII maximum quantum efficiency) as measured by Fv/Fm values on dark-adapted camellia plants. Data were collected using a Li-COR 6400XT leaf chamber fluorometer (Li-COR, Lincoln, NE) to evaluate the potential phytotoxicity of camellia to foliar applied chlorine dioxide (ClO2) and hydrogen dioxide (H2O2), with or without sarcosinate surfactant with consecutive spray applications. Chlorophyll activity (Fv/Fm) of dark adapted foliage was greater when ClO2 and H2O2 were applied with sarcosinate surfactant to camellia foliage compared to treatments not containing sarcosinate surfactant. Chlorophyll activity decreased with increasing concentrations of ClO2 without sarcosinate. Higher Fv/Fm across seven measurement intervals were observed in ClO2 treatments compared to H2O2 treatments at the same concentration. Visual injury of camellia foliage increased with each of the five subsequent spray applications; however, foliar injury did not exceed a marketable threshold for most treatments, until after four consecutive spray applications at 400 mg·L-1 ClO2, with or without surfactant. This study demonstrated that Electro-BioCide at a rate predicted to eradicate Phytophthora ramorum (200 mg·L-1) should not visually damage camellia plants until after five consecutive spray applications. These findings indicate that Electro-BioCide has the potential to be implemented as a preventative foliar treatment for defense against foliar plant pathogens, without concern for detriment to plant health.